Education with the Lunar Theme - Melia, Matthew James; Gray, Sean Patrick; Tersoo-Ivase, Jighjigh (Worcester Polytechnic Institute, 2012)
Our goal was to design a project incorporating the lunar theme that could be - presented to the students with minimal inconvenience to the faculty. This project made use - of multiple presentations to enhance students' interests in scientific topics related to the - lunar theme. It was our hope that these presentations would enrich the students' learning - experience and motivate them to research these topics in their own time. Our final goal was - for teachers to be able to use this project to motivate their students.
Keywords: Educational surveys--Design; Teaching